PEMANFAATAN LIMBAH PENETASAN AYAM BROILER SEBAGAI SUMBER PROTEIN PAKAN IKAN - SAHRUL ALIM; NURI MUAHIDDAH; DAMAI DINIARIWISAN (GANEC SWARA, 2024)
Processing hatching waste in the form of infertile eggs and DOC requires several stages. The first stage is break the infertile egg using a wooden stick that the egg contents and shell can be separated. Meanwhile, for the processing of DOC waste, the feathers are separated fisrt to simplify the grinding process. After the egg breaking process, the shell is separated from the egg liquid. The process of filtering the shells uses a sieve with a mess size 2000. The process of preparing raw materials in the form of hatching waste is carried out using the cooking method using a stove with a temperature between 130℃ - 150℃ with a cooking time ranging from 2 - 3 hours. The next process is drying the results of cooking infertile eggs under the sun for 3 days. After that reduce the water content in the material. After drying, the oven process is carried out that the material is durable and does not become moldy during storage. This process is carried out for 1 – 2 hours, that the nutritional content is not damaged due to the long oven process. The results of proximate analysis of hatchery waste meal (TLP) showed that the water content was 11.32%, the ash content was 0.42%, crude fat was 35.74%, crude fiber was 0.08% and protein was 37.13%. This shows that TLP can be used as a protein for fish feed